Pelatihan Service Attitude Dalam Meningkatkan Sumber Daya Manusia (SDM) Pada Karyawan Di Kotta Hotel Semarang - Ahmad Mansur; Syamsul Hadi; Umar Abdul Jabbar (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
Jembrak In this era of globalization, service is the main key in building positive relationships between service providers and consumers. One of the critical aspects in providing services is attitude or Service Attitude, namely the attitude shown by individuals or organizations in providing services to the community. Service Attitude is not just about providing services, but also creating positive experiences and added value for the communities served. In this context, research and in-depth understanding of Service Attitude becomes very important. Ethics is a branch of philosophy that considers concepts such as morality, values, and human actions. This includes consideration of what is right and wrong, both in relationships between individuals and in social and professional contexts, improving Human Resources (HR) for employees at Kotta Hotel Semarang.